Analysis of Pangkep Regency Groundwater Potential Through the Use of the Overlay Method Geographic Information System - Nasrul; Muhammad Taufan Nuryadin; Mulianti; Sri Wahyuni Hasrin; Mat Rasul; Ferigo Taufani Tri Hakiki (PT. Lontara Digitech Indonesia, 2024)
The increase in population results in an increase in the amount of water supply needed to carry out all activities of the population. Groundwater is a very important alternative source, especially during the dry season. This research aims to determine the distribution of groundwater potential in Pangkajene Regency and the islands which can be used as a reference and information regarding areas that have groundwater potential. By using the overlay method through the use of geographic information systems. This method is carried out by scoring each parameter used, namely giving a value and weighting according to the classification of each parameter. The analysis process was carried out with the help of the ArcGIS 10.8 mapping application. Based on the results of the analysis carried out in this research, it was found that Pangkep Regency as a whole has a moderate level of groundwater potential, this can be seen from the percentage of 60.26% of the total area of ​​Pangkajene Regency or around 476.4302954 km2 has groundwater potential. which is being. In this case, the government needs to carry out regular monitoring and evaluation of groundwater conditions in areas with medium potential including Tondong Talassa, Minasa Tene, Pangkajene, and Bungoro sub-districts to ensure that the quality and quantity of groundwater do not decline to low or very low. As well as carrying out detailed exploration and inventory of groundwater potential in areas with high levels such as in the Mandalle, Marang, and Labakkang subdistricts.